From here to free trade : essays in Post-Uruguay Round trade strategy - Preeg, Ernest H. (Univ. of Chicago P. ChicagoUS, 1998)
Assesses U.S. interests in economic globalization and examines recent steps toward free trade at the multilateral and regional levels. Offers an in-depth critique of U.S. regional free trade objectives in the Americas , the Pacific, and possibly with Europe. Presents a multilateral/regional synthesis for going from here to free trade over the coming decade.